Does Uncertainty Affect the Banks’ Non-Performing Loans/Non-Performing Finance in the MENA Region? A Comparison Study Between Conventional and Islamic Banks in the MENA Regions - Shadi Ratib Mohammad Aledeimat; Murad Abdurahman Bein (SAGE Open)
This study investigates the impact of uncertainties on the non-performing loans/ finance (NPL/NPF) of conventional and Islamic banks in the MENA region using data from 2005 to 2022. Based on inclusion and exclusion criteria and the purposive sampling technique, 92 banks were selected from 13 MENA countries, 42 of which are Islamic and 50 of which are conventional banks. The study used two estimation methods: Augmented Mean Group (AMG) and two-step Generalized Method of Moments (GMM) to estimate the relationship between uncertainty and NPL/NPF. These estimation methods were chosen for their ability to provide unbiased results in the presence of cross-sectional dependence and deal with endogeneity. The study revealed that world pandemic uncertainty had a negative and significant influence on the NPL of conventional banks while showing a positive and significant influence on the NPF of Islamic banks. US trade policy uncertainty was found to have a negative and significant influence on the NPL of conventional banks. In contrast, it exhibited a positive and significant influence on the NPF of Islamic banks. We discovered a positive and significant influence of US sovereign debt risk uncertainty on the NPL/NPF of conventional and Islamic banks in the MENA region. The findings revealed a negative and significant influence of oil price uncertainty on the NPL/NPF of conventional and Islamic banks in the MENA regions. These findings reassure us that bank in the MENA region should adopt and tailor risk strategies based on sector-specific responses, engage in proactive risk monitoring, and maintain loan quality amid economic uncertainties.